How the passage of laws highlights barriers to access to healthcare and the possibility of breaking them down with an outreach project (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
The purpose of this article is to disseminate the outreach activities of the Dentistry program at the Universidad Nacional de Rio Negro (UNRN) within the framework of the "Inclusive Dental Clinic" (hereinafter IDC) from 2019 to the present.The two central axes of the IDC are:-To improve the oral health status of people belonging to the LGBTIQ+ community en the Alto Valle, region of the Province of Río Negro.- To promote teaching and learning among IDC participants on issues of gender, rights and health.The aim is to raise awareness about the dental practices implemented by users and the training workshops for participating healthcare providers, as well as the impact on the local population, each participant´s environment, and the academic community at the Dental School in the city of Allen, Provincia de Rio Negro, where the activities are carried out.
Keywords: gender; rights; health; university outreach